Woman manager : developing essential skills for success - Sitterly, Connie (Crisp Pub. Menlo ParkUS, 1993)
Discusses the environment in today's workplace. Presents essential management skills i.e. time management, communicating for results, negotiation, decision making and problem solving. Describes challenges women face as leaders in the workplace. Includes: understanding power and politics, sexual harassment, and managing stress.